Coagulation Factor XI Promotes Distal Platelet Activation and Single Platelet Consumption in the Bloodstream Under Shear Flow. Issue 3 (March 2016) - Zilberman-Rudenko, Jevgenia; Itakura, Asako; Wiesenekker, Chantal P.; Vetter, Ralf; Maas, Coen; Gailani, David; Tucker, Erik I.; Gruber, András; Gerdes, Christoph; McCarty, Owen J.T.
Abstract : Objective—: Coagulation factor XI (FXI) has been shown to contribute to thrombus formation on collagen or tissue factor–coated surfaces in vitro and in vivo by enhancing thrombin generation. Whether the role of the intrinsic pathway of coagulation is restricted to the local site of thrombus formation is unknown. This study was aimed to determine whether FXI could promote both proximal and distal platelet activation and aggregate formation in the bloodstream. Approach and Results—: Pharmacological blockade of FXI activation or thrombin activity in blood did not affect local platelet adhesion, yet reduced local platelet aggregation, thrombin localization, and fibrin formation on immobilized collagen and tissue factor under shear flow, ex vivo. Downstream of the thrombus formed on immobilized collagen or collagen and 10 pmol/L tissue factor, platelet CD62P expression, microaggregate formation, and progressive platelet consumption were significantly reduced in the presence of FXI function-blocking antibodies or a thrombin inhibitor in a shear rate– and time-dependent manner. In a non-human primate model of thrombus formation, we found that inhibition of FXI reduced single platelet consumption in the bloodstream distal to a site of thrombus formation. Conclusions—: This study demonstrates that the FXI–thrombin axis contributes to distal platelet activation and procoagulant microaggregate formation in the blood flow downstream of the site of thrombus formation. Our data highlight FXI as a novel therapeutic target for inhibiting distal platelet consumption without affecting proximal platelet adhesion. Abstract : Supplemental Digital Content is available in the text.